Fracture Micromechanisms Evaluation of High-Strength Cast Irons Under Thermomechanical Fatigue Conditions - Bon D.G. (2020)
© 2019, American Foundry Society.The truck industry has constantly searched to increase the performance of heavy-duty diesel vehicles, either by reducing weight and the size of the engines, or by increasing their power. In this sense, higher strength grades of cast iron have been developed and tested under thermomechanical conditions, and the results have been positive, since life under such conditions has increased significantly. The purpose of this paper was to shed some light on the fracture micromechanisms acting during crack nucleation and growth under thermomechanical loading conditions, in two cast iron types for use in cylinder head manufacturing, namely gray iron grade 300 (GI 300) and compacted graphite iron grade 500 (CGI 500). The results were compared with those from the standard grades GI 250 and CGI 450. In both gray and compacted graphite irons, fractographic examination showed that the crack starts at graphite tips, grows through the graphite skeleton inside a eutectic cell, and progresses by the coalescence of multiple fatigue cracks from one eutectic cell to another, fracturing the matrix at eutectic cell boundaries. In CGI 500, the graphite in eutectic cells ended with a change in the graphite shape, from vermicular to a round shape end. This brings additional difficulties for the crack propagation process, and, together with the rough interface graphite/matrix and with the thick eutectic cell boundaries, it explains the outstanding thermomechanical results with the CGI 500.